2023
DOI: 10.5194/gmd-16-1641-2023
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic ammonia emission model and the online coupling with WRF–Chem (WRF–SoilN–Chem v1.0): development and regional evaluation in China

Abstract: Abstract. The volatilization of ammonia (NH3) from fertilizer application and livestock wastes is an overwhelmingly important pathway of nitrogen losses in agricultural ecosystems and constitutes the largest source of atmospheric NH3. The volatilization of NH3 highly depends on environmental and meteorological conditions, however, this phenomenon is poorly described in current emission inventory and atmospheric models. Here, we develop a dynamic NH3 emission model capable of calculating the NH3 emission rate i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Ammonia (NH 3 ) volatilization from fertilization and animal waste is an extremely important mode of nitrogen loss in agricultural ecosystems and is the largest source of atmospheric NH 3 . The volatilization of NH 3 is highly dependent on environmental and meteorological conditions [43].…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia (NH 3 ) volatilization from fertilization and animal waste is an extremely important mode of nitrogen loss in agricultural ecosystems and is the largest source of atmospheric NH 3 . The volatilization of NH 3 is highly dependent on environmental and meteorological conditions [43].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 presents a computational algorithm and procedure of risk assessment. According to typical studies on the modeling of ammonia leakage and release [64][65][66][67][68][69][70][71][72][73][74][75][76][77], the common algorithmic diagram for the computational analysis of ammonia leakage is shown in Figure 5, and the computational algorithm and procedure are presented in Figure 6. The six steps required to use computational fluid dynamics (CFD) for the modeling and consequence analysis of ammonia leakage or accidents include the following:…”
Section: Cfd and Theorical Analysismentioning
confidence: 99%
“…The algorithm in Figure 7 below describes a procedure for risk analysis using riskbased methods similar to those seen in [78][79][80][81][82][83]. According to typical studies on the modeling of ammonia leakage and release [64][65][66][67][68][69][70][71][72][73][74][75][76][77], the common algorithmic diagram for the computational analysis of ammonia leakage is shown in Figure 5, and the computational algorithm and procedure are presented in Figure 6. The six steps required to use computational fluid dynamics (CFD) for the modeling and consequence analysis of ammonia leakage or accidents include the following: (i) Identify the simulation case: This step is to clarify the purpose of the simulation and which leakage/release case will be addressed.…”
Section: Cfd and Theorical Analysismentioning
confidence: 99%
“…Research indicates that urban NH 3 concentrations in eastern China are also underestimated, but the magnitude is smaller than in Beijing. 37,38 Research methodologies in this study can be applied to unveil mechanisms of underestimation in other cities. Dense and regular NH 3 monitoring is the basis for comprehensive model evaluation, improved air quality modeling, and subsequent science-informed policymaking with respect to clean air.…”
Section: Inversion Estimate Of Summertime Nh 3 Emissions For Beijing ...mentioning
confidence: 99%
“…Even for a larger region such as the NCP, studies using different methods disagree on whether NH 3 emissions in the NCP are underestimated or overestimated. 35,36 In addition, previous research reported that model-simulated gaseous NH 3 concentrations were biased low against groundbased or satellite observations in Nanjing and Beijing, 37,38 in California 39−41 and near large source regions across the United States, 42 and in Paris, Mexico City, and Toronto 43 during the warm season. However, few studies have attributed such biases to uncertainties in emissions, chemistry, meteorology, or regional transport quantitatively, especially for China.…”
Section: Introductionmentioning
confidence: 99%